Channel Modification Engineering by Plasma Processing in Tin-Oxide Thin Film Transistor: Experimental Results and First-Principles Calculation. (22nd February 2017) - Chiu, Y. C.; Chen, P. C.; Chang, S. L.; Zheng, Z. W.; Cheng, C. H.; Liou, G. L.; Kao, H. L.; Wu, Y. H.; Chang, C. Y.
Abstract : In this paper, we investigated the effects of oxygen plasma treatment on tin oxide (SnOx ) thin film transistors (TFTs). By using oxygen plasma treatment on SnOx active channel layer, excess oxygen was incorporated to the channel layer and converted oxygen-deficient SnOx to oxygen-rich SnO2-x, which in turn causes the device operation from p -type to n -type. Tuning the different exposure time of oxygen plasma, the optimal TFT device exhibits n -type properties with an on/off current ratio of 2.6 × 10 4, a very high field-effect mobility of 89 cm 2 V −1 s −1, and a threshold voltage of −0.95 V. Furthermore, the effects of oxygen plasma treatment on band structure, density of states and electron density difference of the SnOx channel layer were performed by the first-principles calculation using density functional theory. The results show that the oxygen plasma treatment approach has high potential for high-performance TFT applications.